The antecedents of stock prices in Malaysia / Nur Hazirah Fadzil - Fadzil, Nur Hazirah (Faculty of Business Management, 2017)
The purpose of this study is to determine the antecedents of stock prices in construction companies in Malaysia based on the market valuation. The variables that being used in this study are earnings per share (EPS), price earnings ratio (P/E) and dividend yield (DY) as independent variables while stock price (SP) as dependent variable. The company that being choose in this study based on top 10 companies that has high market capital out of 45 companies that being listed in Bursa Malaysia. However, due to the unavailability of the data in Thomson One Reuters, only 6 companies that being selected in this study. This study used descriptive statistic, unit root test, regression using panel data and diagnostic test in order to test the hypothesis. The data is collected from 1st July 2012 until 31st December 2015. All these three variables show positive and significant effect towards stock prices. It means that all these variables are the antecedents of stock prices in construction companies in Malaysia. But, in diagnostic test the autocorrelation and residual are not normally distributed. It means that the result from these findings might not be reliable to use in another period. This study is important since it will give knowledge towards the investor in order to make the decision on investment since construction industry is one of fragile industry in Malaysia.